Recycling of LiMO2 cathode materials by a chlorination-based Li extraction technique - Jeon, Min Ku; Kim, Sung-Wook; Kim, Hyungsub; Kim, Kyoung Sun (The Korean journal of chemical engineering, 2022)
The recycling of Li(Ni 1/3 Co 1/3 Mn 1/3 )O 2 (NCM) and LiCoO 2 (LCO), which are cathode materials for Li-ion batteries, was demonstrated via a chlorination-based Li extraction technique. The recycling process follows a chlorination - washing/filtering - drying - mixing - re-synthesis process. Around 86% of Li was removed through the chlorination - washing/filtering steps. The resulting transition metal oxide powder was dried and then mixed with Li 2 CO 3 , a Li precursor. Re-synthesis experiments were conducted at 900 °C for 24 h and the weight of the final products was 88.5 and 88.0 wt% of their input amounts in NCM and LCO, respectively. Structural changes were analyzed by X-ray diffraction to confirm the absence of impurity phases in the re-synthesized specimens. Electrochemical evaluation revealed that the re-synthesized NCM and LCO exhibit corresponding initial specific capacities of 157 and 153 mAh/g.